2023
DOI: 10.1136/bcr-2022-254429
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic hamartoma: a cause of precocious puberty

Abstract: Hypothalamic hamartomas are uncommon congenital malformations that present as precocious puberty, gelastic seizures and/or psychiatric disorders. Characteristic changes in MRI scans lead to a diagnosis. Treatment may include surgery or gonadotropin-releasing hormone agonists (GnRHa) depending on clinical manifestations.Here, we describe a case of hypothalamic hamartoma diagnosed in a girl in middle childhood, who presented with early development of secondary sexual characteristics. Physical examination, hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Approximately 75%-90% of CPP cases in girls are primary, while 40%-75% of CPP cases in boys are associated with cranial diseases [14,15] . Researchers have demonstrated that the risk of CPP in children with neurological disease is 20 times higher than that in healthy children (Figure 3C) [16][17] . Encephalic organic diseases may cause CPP by inhibiting GnRH synthesis or by increasing intracranial pressure affecting the hypothalamus or pituitary [18] .…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 75%-90% of CPP cases in girls are primary, while 40%-75% of CPP cases in boys are associated with cranial diseases [14,15] . Researchers have demonstrated that the risk of CPP in children with neurological disease is 20 times higher than that in healthy children (Figure 3C) [16][17] . Encephalic organic diseases may cause CPP by inhibiting GnRH synthesis or by increasing intracranial pressure affecting the hypothalamus or pituitary [18] .…”
Section: Discussionmentioning
confidence: 99%